Study of nonlinear differential inclusions with generalized order and its applications - HADJADJ, Elhabib (Universty Of El-oued جامعة الوادي, 2024)
In this thesis, we studied a set of fractional differential inclusion problems under boundary and initial conditions, using fixed point theorems as a strategy. Initially, we proved the existence of solutions for nonlinear fractional differential inclusions in Banach spaces. After that, we investigated the existence and uniqueness of the solution and the topological structure of solutions to fractional differential inclusions in Lebesgue and Sobolev spaces. Finally, we discussed the existence and uniqueness of solutions for fractional differential inclusions under initial conditions in unbounded domains. The proof for each problem is based on the formation of a multifunction whose elements are integral equations, which are the basis of fractional differential equations. The second side is a function of the multifunction present in the second side of the fractional differential inclusions. After this, it is proven that it possesses a fixed point.في هذه الاطروحة، قمنا بدراسة مجموعة من الجمل التفاضلية الاحتوائية تحت شروط ابتدائية وحدية باستخدام استراتيجية النقطة الصامدة. في البداية اثبتنا وجود حلول للاحتواءات التفاضلية الكسرية في فضاءات لوبيغ وسوبولاف، وفي الأخير ناقشنا وجود ووحدانية الحلول للاحتواءات التفاضلية الكسرية تحت شروط ابتدائية في ميادين غير محدودة. ترتكز الاثباتات في كل جملة على تشكيل دالة متعددة القيم عناصر قيمها معادلات تكاملية والتي هي في الأصل معادلات تفاضلية كسرية طرفها الثاني دالة من الدالة المتعددة القيم الموجودة في الطرف الثاني من الاحتواءات التفاضلية الكسرية، بعد ذلك اثبات أنها تملك نقاط صامدة.
أطروحة دكتوراه تخصص الرياضيات في العلوم الدقيقة
Keywords: Intégrale de Riemann-Liouville; dérivée de Riemann-Liouville fonction multivoque; problèmes aux limites et aux valeurs initiales; sélection mesurable; théorème du point fixe; inclusion différentielle fractionnaire; تكامل واشتقاق ريمان ليوفيل، دالة متعددة القيم، الجمل ذات القيم الحدية والابتدائية، اختيار قابل للقياس، نظرية النقطة الصامدة، الاحتواءات التفاضلية الكسرية